2015
DOI: 10.1007/s11739-015-1222-8
|View full text |Cite
|
Sign up to set email alerts
|

Theme-based teaching of point-of-care ultrasound in undergraduate medical education

Abstract: A handful of medical schools have developed formal curricula to teach medical students point-of-care ultrasound; however, no ideal method has been proposed. The purpose of this study was to assess an innovative theme-based ultrasound educational model for undergraduate medical education. This was a single-center cross-sectional study conducted at an academic medical center. The study participants were 95 medical students with minimal or no ultrasound experience during their third year of training. The educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Almost all of our students agreed that US training should begin in medical school in accordance with other studies. 5,26 Our study had several limitations. As we all know, US competency comprises two parts, which includes image acquisition and image interpretation.…”
Section: Mean Score Sd Pmentioning
confidence: 89%
“…While some medical schools have achieved this through introduction of ultrasound into early physical examination and anatomy courses [11][12]19 , one-time seminars 14,15 and 4 th year electives 16 , these approaches may not work across all medical school curricula. Previous success had been reported with implementation of a theme-based format when similar short blocks of time were used for educational purposes with point-of-care ultrasound (POCUS).…”
Section: Discussionmentioning
confidence: 99%
“…Previous success had been reported with implementation of a theme-based format when similar short blocks of time were used for educational purposes with point-of-care ultrasound (POCUS). 15 Additionally, ultrasound at the graduate medical education (GME) level has shown to be most successful when it has employed a combination of ultrasound faculty directed didactics and hands-on experience. 18 Within a review of emergency medicine resident competencies of POCUS, it was found that programs that had 15 hours of didactic education and a formal ultrasound rotation produced residents with higher test scores on standardized ultrasound testing and improved competancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation